Science Process Skills in Science Education of Developed and Developing Countries: Literature Review - Mushani, Mercy (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2021)
The purpose of this literature review is to analyze and evaluate the research studies conducted on science process skills (SPS) in science education in the context of developed and developing countries. A follow-up to this study will investigate teacher facilitation of SPS development at Primary School level in Zambia. The method carried out in this study is a literature review. It involved analyzing and synthesizing some research work already conducted globally, considering the educational significance of SPS. The search was limited to peer-reviewed journal articles written in English and whose full papers were available on the databases. Additionally, the articles were published between 1987 and 2018 because SPS's teaching and learning has been prevalent in research since the early 1980s. In total, 198 articles were found as a result of the initial search. The researcher screened abstracts of these articles to judge their relevance, and from this screening process of abstracts, 40 papers have been included for review. Reviewed study trends on SPS development conducted from developed and developing countries focusing on three vantage points: science curriculum, teacher education and the 21st Century Learning. Based on the findings, more research studies on SPS in science education are carried out in developed countries than developing ones. The review findings indicate uneven inclusion of SPS in the science curriculum documents and the curriculum implementation at all science education levels. Lastly, results display few studies on SPS education regarding 21st Century Learning conducted in developed and developing countries. Concerned education bodies must take appropriate and reasonable exploits on teacher training of SPS education and the balanced inclusion of SPS in the science curriculum and its implementation into consideration. SPS still champions the development of other skills individuals are supposed to possess in this 21st-century era. Hence, SPS education in science education remains a need for both developed and developing countries.